Leisure Mass Media & Social Structure - "Modi, Ishwar" (Jaipur, 1985)
This book examines the complex phenomenon of leisure both as a concept and an element of social change. This pioneering study attempts to understand the development of the concept of leisure by using four theoretical perspectives: the metaphysical cultural, socio-psychological, and the sociological and in the process demystyfies and establishes the erroneousness of such notions that leisure existed in its truest sense only in ancient Greece during the time of great philosophers Plato and Aristotle, and neither before nor after; or that leisure is essentially the product only of the civilizations born from the industrial revolution. Contrary to such assertions Dr. Modi holds that leisure exists universally and that it has a dynamic character. While it is structural in nature it is cultural in orientation and operation. Through a series of brilliant comparative sociological historiography of some societies and groups which existed during different historical periods both in the West as well as in India Dr. Modi firmly establishes that there exists a clear concomitance between the social structure and the structure of leisure of a society and that changes in either of the two influences each other.
Keywords: Communication